Inspiration amidst crisis: e-learning in a medical school of Nepal during COVID-19 pandemic - Pandey, Merina; Aryal, Bibek (Canadian Medical Education Journal, 2020)
The Coronavirus disease (COVID-19) pandemic continues to shut down colleges and universities including medical schools all over the world, thus pushing medical schools to seek e-learning to maintain continuity of curriculum. Although developed countries are comfortable learning through the internet, low-income countries like Nepal with limited experience in e-learning have used this lockdown as an opportunity to develop online classes. This crisis has clearly revealed the importance of e-learning in for medical educators in Nepal to disseminate knowledge beyond the restrictions of geography and other barriers.